Iodat Analysis Content in Cooking Ingredients Using Iodometry and X-ray Fluorescence Methods. - Saksono, Nelson (UI Scholars Hub, 2002)
Iodat Analysis Content in Cooking Ingredients Using Iodometry and X-ray Fluorescence Methods. Salt iodization program using iodine fortification into salt method is the best method that is effective and economical to overcome the problems caused by iodine deficiency. However in, its development there are some issues clamed that the use of iodized salt is ineffective since iodine content reduces, even disappear when the salt mix with other cooking ingredients. In order to investigated the existence of iodine in cooking ingredients, a research applying iodometry and X-ray fluorescence methods was carry out. The result obtained by iodometry method showed decreases in iodine content in each ingredient, as chili was 75,5 %, ketumbar was 51,43 %, and pepper was 20.99 %. On the other hand, the X-ray Fluorescence measurement showed the iodat deficiency in chili was 12.84 %, ketumbar was 6.42 %, and pepper was 1.14 %. The difference in the result of iodat deficiency can be caused by difference in principle and possessed by them. Iodometry only can analyze iodine in iodat form, while in cooking ingredients iodat may exist in various compound. X-ray Fluorescence can analyze iodat in some compounds so that the complicated matrix ingredient with not interfere the measurement.